1969
DOI: 10.1002/jez.1401710210
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic control of antler cycles in deer. II. Alterations in amplitude

Abstract: Deer native to temperate zones grow new antlers each year in synchrony with the annual photoperiodic cycle. When the amplitude of this cycle is reduced from normal winter and summer solstices ( a t 42" latitude) of nine and fifteen hours to as little as eleven and one-half and twelve and one-half hours (equivalent to about 9" latitude), sika deer still tend to grow antlers on schedule, even when that schedule is accelerated.Deer exposed to days of constant length for prolonged periods of time fail to replace t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…la) (Gillet, 1904;Bedford, 1951;Petzsch, 1959;McEwan, 1968;Suttie & Kay, 1985), suggesting that the stag must have experienced two reproductive cycles. In addition, Goss (1976) found that sika deer (C. nippon) kept on an artificial photoperiod in which daylength decreased or increased by 2 h every 4 months cast and regrew their antlers each time the photoperiod changed, irrespective of the direction of change. If it is assumed that a full cycle of antler development is an indicator of a cycle of reproductive development, then it is clear that the deer in Goss's (1969) (Lincoln, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…la) (Gillet, 1904;Bedford, 1951;Petzsch, 1959;McEwan, 1968;Suttie & Kay, 1985), suggesting that the stag must have experienced two reproductive cycles. In addition, Goss (1976) found that sika deer (C. nippon) kept on an artificial photoperiod in which daylength decreased or increased by 2 h every 4 months cast and regrew their antlers each time the photoperiod changed, irrespective of the direction of change. If it is assumed that a full cycle of antler development is an indicator of a cycle of reproductive development, then it is clear that the deer in Goss's (1969) (Lincoln, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…The loss in synchrony of spawning between the different individuals in each of the LL and 18L:6D regimes is also suggestive of "a freerunning" rhythm. Possibly, the accepted period limits of circannual cycles should be wider for even the study of Goss (1969) on antler growth in sika deer, which is often cited as a model example of a circannual rhythm, also includes animals with two antler growth cycles per year.…”
Section: Discussionmentioning
confidence: 98%
“…Under ambient conditions these cycles are closely entrained by the natural seasonal alterations in daylength. Similar patterns of entrainment can also be achieved under accelerated seasonal light cycles (Goss 1969;Bromage et aL 1982a;Elliott et aL 1984;Gwinner 1981), but not under constant photoperiod regimes. This suggests that the seasonallychanging daytength normally provides a sequence of photoperiodic cues (i.e.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Females of tropical species can give birth at any time of the year, and males can grow antlers at any time of the year. Every 12 months, however, each male sheds and replaces his antlers (Goss 1969a(Goss , 1969b. Those interested in antlers are also directed to Goss (1963Goss ( , 1968 and Jaczewski (1954).…”
mentioning
confidence: 99%